Tofacitinib prevents depressive-like behaviors through decreased hippocampal microgliosis and increased BDNF levels in both LPS-induced and CSDS-induced mice - Gao Ya-nan; Pan Kai-jun; Zhang Yong-mei; Qi Ying-bei; Chen Wen-gang; Zhou Ting; Zong Hai-chao; Guo Hao-ran; Zhao Jin-wen; Liu Xing-chen; Cao Zi-tong; Chen Ze; et al. (Acta Pharmacologica Sinica, 2025)
Depressive disorders are a global mental health challenge that is closely linked to inflammation, especially in the post-COVID-19 era. The JAK-STAT pathway, which is primarily associated with inflammatory responses, is not fully characterized in the context of depressive disorders. Recently, a phase 3 retrospective cohort analysis heightened that the marketed JAK inhibitor tofacitinib is beyond immune diseases and has potential for preventing mood disorders. Inspired by these clinical facts, we investigated the role of the JAK-STAT signaling pathway in depression and comprehensively assessed the antidepressant effect of tofacitinib. We found that aberrant activation of the JAK-STAT pathway is highly conserved in the hippocampus of classical depressive mouse models: LPS-induced and chronic social defeat stress (CSDS)-induced depressive mice. Mechanistically, the JAK-STAT pathway mediates proinflammatory cytokine production and microgliosis, leading to synaptic defects in the hippocampus of both depressive models. Remarkably, the JAK inhibitor tofacitinib effectively reverses these phenomena, contributing to its antidepressant effect. These findings indicate that the JAK/STAT pathway could be implicated in depressive disorders, and suggest that the JAK inhibitor tofacitinib has a potential translational implication for preventing mood disorders far beyond its current indications.